From High-level Descriptions to VLSI Circuits - Greenstreet, Mark R.; Staunstrup, Jørgen (DAIMI Report Series, 1988)
This paper presents a high-level language for describing VLSI circuits designed as a collection of asynchronous concurrent processes. This language is called ''Synchronized Transitions'' , and it can be used to describe designs from very high levels of abstraction down to the gate level design. Both synchronous and asynchronous/self-timed circuits can be described, and it is not necessary to choose a particular type of circuitry in the early phases of a design. ''Synchronized Transitions'' programs may be used for experimenting with (simulating) a design at several levels, e.g., to explore different high-level decisions or to verify the gate level. By observing certain constraints in a ''Synchronized Transitions'' program, it is possible to systematically transform the program into an efficient layout.